Uji Efektivitas Beberapa Jenis Ekstrak Daun Tanaman terhadap Populasi Hama Ulat Krop Kubis Crocidolomia pavonana F. (Lepidoptera: Pyralidae) di Lapang - BARITA, EKA BHUWANA BONAULI; SUMIARTHA, I KETUT; SRITAMIN, MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Effectiveness Of Some Extract Of Plants Leaf To Cabbage Crop Caterpillar Crocidolomia pavonana F. (Lepidoptera: Pyralidae) In The Field Cabbage crop caterpillar (Crocidolomia pavonana F.) is one of the most important pests in cabbage plants. This caterpillar is capable todecreasing cabbage production. This study was conducted in order to determinethe ability of some extracts of leaf plants such as: Chromolaena odorata L., Lantana camara L, Tithonia diversifoliaHemsl., and Nicotiana tabacum L., to suppress the development of the population, the most effective leaf extract against Crocidolomia pavonana F.and its effect on quality of cabbage leaves. This study used Randomized Block Design (RBD) with 5 treatments and replicated 5 times. This study was done from November 2017 to February 2018. The results showed that from the 4 plants extracts that significantly affect the population ofCrocidolomia pavonana F compare to control treatment. The highest population decline was found in C. odorata leaf extract of 1.8 /plants and T. diversifolia of 1.8 /plant. In the effectivity test of leaf extract proved able to suppress population of C. pavonana with different potency. The result of observation of cabbage crop weight showed that the treatment of plant extract had significantly effect on the weight of cabbage. Treatment with C. odorata leaf extract had higher average cabbage weight compared to other treatment which was 2.1 kg, while the lowest weight of cabbage was 1.4 kg. The average yield of cabbage crop quality with different quality categories. In treatment with C. odorata extract, L. camara, T. diversifolia, and N. tabacum resulted in crop quality with quality category 2.